2016
DOI: 10.1002/aenm.201502468
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic Materials and Devices Based on the Alloyed Kesterite Absorber (AgxCu1–x)2ZnSnSe4

Abstract: narrows the CZTSSe band gap. The low energy barrier to Cu/Zn antisite formation is related to the similarity between the covalent radii of Cu and Zn. [ 4 ] The elevated processing temperatures (550-600 °C) needed to form large-grained CZTSSe fi lms (and peak device effi ciencies) provide the required thermal energy to randomize Cu and Zn in the unit cell, leading to a high density of antisite defects. [ 5 ] If disorder is the primary cause of performance loss in CZTSSe, then suppressing or eliminating it might… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
220
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(244 citation statements)
references
References 31 publications
15
220
1
3
Order By: Relevance
“…The apparent grain size increases from hundreds of nanometers to several microns. The effect of Ag on the intragrain defects and crystal growth is discussed for both ACZTS [22], [23], [25] and ACIGS [20]. Gershon et al [23] and Su et al [25] found largely increased grain size for ACZTS for a Ag/(Ag + Cu) ratio of ∼10%.…”
Section: A Structural and Morphological Properties Of Acts Absorber mentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent grain size increases from hundreds of nanometers to several microns. The effect of Ag on the intragrain defects and crystal growth is discussed for both ACZTS [22], [23], [25] and ACIGS [20]. Gershon et al [23] and Su et al [25] found largely increased grain size for ACZTS for a Ag/(Ag + Cu) ratio of ∼10%.…”
Section: A Structural and Morphological Properties Of Acts Absorber mentioning
confidence: 99%
“…Alloying chalcopyrite materials with Ag has been shown to have several advantageous properties for kesterite and Cu(In,Ga)S 2 (CIGS) absorbers [19]- [26] [(Ag, Cu) 2 ZnSnS 4 (ACZTS) and (Ag,Cu)(In,Ga)S 2 (ACIGS)]. Ag replaces Cu in these materials, which increases the band gap [19], [23], [24], [26], decreases the p-type doping [23], as well as reduces intragrain defects and defect states [19]- [21], [23], [26]. All these effects may be beneficial for CTS as well.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, current density falls significantly with the higher thickness of CZTS (Figure 2(a)) because of the reduced optical power absorption in the bottom cell. Thus, higher thickness of [19] 7 [18] 8.5 [17] 7 [16] Band gap (eV) 1.9 [14] 1.45 [18] 0.97 [17] 0.9 [16] Electron affinity (eV) 3.6 [19] 4.1 [24] 4.05 [17,25] 4.05 [13] Electron effective mass (m e /m o ) 0.37 [14,15] 0.18 [13,16] 0.08 [17] 0.07 [13,16] Hole effective mass (m p /m o ) 1.68 [14] 2 [13,16] 0.3 [17] 0.2 [13,16] Electron mobility (cm 2 V À1 s À1 ) 3 0 [26] 40 [21,24] 75 [23] 145 [13,21] Hole mobility (cm 2 V À1 s À1 ) 1 0 [27] 25 [21] 1 [17,23] 35 [13,21] Acceptor concentration (cm…”
mentioning
confidence: 99%
“…was previously achieved at 45 and 0% ratio of Ag/(Ag þ Cu) in ACZTSe material system, respectively. [17] The detailed design of the bottom cell can be found in Supporting Information (Section S2) . The thicknesses of ZnO, ZnS, and CZTSe in the bottom cell are 70, 100, and 200 nm, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation